2017
DOI: 10.1111/1475-6773.12733
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐Ethnic Coverage Disparities among Latinos and the Effects of Health Reform

Abstract: Latino subgroups show marked heterogeneity in baseline coverage rates and responses to the ACA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…6,11 Recent studies that used national data have found that health insurance coverage and access to care after the ACA differ significantly among Latino heritage groups. 3,5 Our study confirms these findings and shows that differences across the groups have narrowed after the implementation of the ACA in California.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…6,11 Recent studies that used national data have found that health insurance coverage and access to care after the ACA differ significantly among Latino heritage groups. 3,5 Our study confirms these findings and shows that differences across the groups have narrowed after the implementation of the ACA in California.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are consistent with the results of other studies and may suggest that health care use is mostly linked to medical need. 3,5 Need could also be a factor related to the lack of significant differences between US-born, documented, and undocumented Latinos in the odds of having had a physician visit. Interestingly, the decomposition analyses showed that observable characteristics accounted for a large proportion of disparities in having physician visits and a usual source of care between Mexicans and other Latinos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Heterogeneous effects within the Latino group were further evidenced by one study examining 2014 Medicaid expansion; the effect size on uninsured rate ranges from −0.0087 to −0.0839 within Latinos and was −0.0427 for whites (Gonzales and Sommers ). But our results contrast with findings that insurance disparities diminished in Oregon based on electronic health record data (Heintzman et al.…”
Section: Discussionmentioning
confidence: 97%
“…; Courtemanche et al. ; Gonzales and Sommers ; Wehby and Lyu ). These results may be due to the fact that minority groups typically have larger proportions of low‐income adults eligible for Medicaid under expansion.…”
mentioning
confidence: 97%